High temperature impression creep behavior and microstructures of wrought ZM21 magnesium alloy. (March 2022) - Ebenezer, D; Koteswara Rao, SR; Vijayan, S; Rajeswari, R
Mg-Zn alloys are promising candidates for their application in automotive, electronics and aerospace applications. For their successful application, one of the performance parameters that needs to be evaluated is their creep behavior at elevated temperatures. Hence this paper evaluates the high temperature creep behavior of wrought ZM21 magnesium alloy by impression test The tests were performed under constant temperature and stress. A flat ended cylindrical punch was used to create impressions. The temperature was varied between 398 K and 598 K while the stresses were varied from 200 MPa to 500 MPa (normalized stress: 0.014 ≤  σ imp / G  ≥ 0.032). A power-law creep deformation was assumed to calculate creep exponent and activation energy using the steady state minimum impression velocity obtained from impression tests. The creep behavior was analyzed with the help of impression creep curves and plastic deformation was analyzed with the help of micrographs. It was found that creep exponent varied between 4.5 and 6 and activation energy between 73.28 and 113.35 kJ/mol were obtained. From the study it was concluded that the creep mechanism involved was pipe-diffusion-controlled dislocation climb.